Pengembangan Media Pembelajaran Diorama Berbasis Augmented Reality (AR) pada Pembelajaran IPAS Kelas V - Elen Kusuma; Hamdan Hamdan; Andri Valen (JOEAI (Journal of Education and Instruction), 2026)
This study aims to develop Augmented Reality (AR)-based diorama learning media to improve students' understanding of Natural and Social Sciences (IPAS) material for grade V of SD Negeri 59 Lubuklinggau. The research method used is Research and Development (R&D) with the ADDIE development model, including the stages of Analysis, Design, Development, Implementation, and Evaluation. The media was tested in terms of validity, practicality, and effectiveness. The validation results showed that the media had a high level of validity, with an average score of 92% from language, media, and material experts, including the very valid category. The practicality of the media was assessed by teachers and students with scores of 92% and 93%, respectively, indicating a very practical category. The effectiveness of the media was demonstrated through pre-tests and post-tests, with an average score increasing from 64 to 83, and an N-Gain value of 0.52, including the fairly effective category. The results of this study indicate that AR-based diorama learning media is feasible, practical, and effective in improving students' understanding of science and natural sciences material, particularly on the topic of the environment and environmental degradation.   Keywords: Augmented Reality, Science and Natural Sciences, Learning Media, Diorama, ADDIE Model